Art as Displacement - Čačinovič, Nadežda (2004)
Art is always an activity of displacement, of a shift, permutation, added reflection.
čeka se objavljivanje zbornika radova s XVI međunarodnog kongresa za estetiku (u Rio de Janeiru, Brazil)
Projekt MZOS
ENG